Genome-wide analysis of RNA-binding proteins co-expression with alternative splicing events in mitral valve prolapse - Zhao, Meng; Zhou, Jingxin; Tang, Yihu; Liu, Mingzhu; Dai, Yawei; Xie, Hui; Wang, Zihao; Chen, Liang; Wu, Yanhu (Frontiers in Immunology, 2023)
Objectives We investigated the possible role and molecular mechanisms of RNA binding proteins (RBPs) and their regulated alternative splicing events (RASEs) in the potential pathogenesis of mitral valve prolapse (MVP). Methods For RNA extraction, we obtained peripheral blood mononuclear cells (PBMCs) from 5 patients with mitral valve prolapse (MVP), with or without chordae tendineae rupture, and 5 healthy individuals. High-throughput sequencing was used for RNA-sequencing. Differentially expressed genes (DEGs) analysis, alternative splicing (AS) analysis, functional enrichment analysis, and RNA binding proteins (RBPs) co-expression with alternative splicing events (ASEs) analysis were conducted. Results The MVP patients had low expression of 198 genes and high expression of 306 genes. All of the down and up-regulated genes were enriched in Gene Ontology (GO) terms and KEGG pathways. Furthermore, MVP was closely associated with the top 10 enriched terms and pathways. In MVP patients, 2288 RASEs were found to be significantly different, and four suitable RASEs (CARD11 A3ss, RBM5 ES, NCF1 A5SS, and DAXX A3ss) were tested. We identified 13 RBPs from the DEGs and screened out 4 RBPs (ZFP36, HSPA1A, TRIM21, and P2RX7). We selected out four RASEs based on co-expression analyses between RBPs and RASEs, including ES of DEDD2, A3SS of ETV6, 3pMEX of TNFAIP8L2, and A3SS of HLA-B. Furthermore, the selected four RBPs and four RASEs were validated by RT-qPCR and showed high consistency with RNA-seq. Conclusions Dysregulated RBPs and their associated RASEs may play regulatory roles in MVP development and may be used as therapeutic targets in the future.